Child Care Choices and Children’s Cognitive Achievement: The Case of Single Mothers - Bernal, Raquel; Keane, Michael P. (Journal of Labor Economics, 2011)
We evaluate the effect of child care versus maternal time inputs on child cognitive development using single mothers from the NLSY79. To deal with nonrandom selection of children into child care, we exploit the exogenous variation in welfare policy rules facing single mothers. In particular, the 1996 welfare reform and earlier state-level policy changes generated substantial increases in their work/child care use. We construct a comprehensive set of welfare policy variables and use them as instruments to estimate child cognitive ability production functions. In our baseline specification, we estimate that a year of child care reduces child test scores by 2.1%.